تنفيذ تعليم مهارة الكلام لتنمية البيئة الاصطناعية في إندونيسيا دراسة الحالة في معهد الإصلاح بجيغاواه مدينة جمبر جاوى الشرقية - Muhammad Ainul Yaqin; Ecky Cahyo Pratama; Achmad Ja'far Sodik (IAIN Bengkulu, 2021)
The ability to make all students able to practice speaking Arabic in everyday life is not easy to apply to every particular institute or educational institution. Because it requires an intensive and patient process. The Institute of Reform is a boy's institute but is competitive and proven. The purpose of this research is: 1. To learn the implementation of speech skill education. 2. Detecting the factors supporting speech skills at the Institute of Reform in Jigwah. 3. Detection of inhibiting factors to learn the skill of speech at the Institute of Reform in Jigwah.This research used the qualitative input, the descriptive approach, which was signed at the Institute of Reform in Jigwah. The way to identify the search detective is in the